Early Energy-Dependent Step in the Entry of Transforming Deoxyribonucleic Acid - Strauss, Norman (1970)
It was found that cyanide can partially reverse as well as arrest the transformation of a newly transformed deoxyribonuclease-treated culture for 6 to 8 min after the addition of the enzyme. These findings strongly suggest that deoxyribonucleic acid which attained deoxyribonuclease-insensitivity is not necessarily in the cell, but stored in some region peripheral to the membrane, and that a rate-limiting, energy-dependent step is required to transport this deoxyribonucleic acid into the cell.